Boosting or Hindering Aid Effectiveness? An Assessment of Systems for Measuring Donor Agency Results. (4th February 2016) - Holzapfel, Sarah
Summary: Amid rising criticism of aid effectiveness coupled with tight budgets in many donor countries at a time of economic crisis, donor agencies are under pressure to deliver value for money and to demonstrate development results. In response to these pressures, more and more donor agencies are adopting standard indicators, which allow for results to be aggregated across interventions and countries, in order to report agency‐wide results. This article analyses the reporting practices of eleven bilateral and multilateral donor agencies and assesses the implications of agency‐wide results measurement systems for aid effectiveness. The analysis shows that the data on aggregate results provided by donor agencies is only of limited informational value and does not provide an adequate basis for holding donor agencies to account. Moreover, reporting on agency‐wide results may have a number of adverse effects. Given the various limitations and risks identified in this article, I suggest that donor agencies should explore complementary options or alternatives to standard indicators in order to meet their reporting requirements. Donor agencies are advised to invest more in rigorous impact evaluations and to raise the transparency of individual interventions. Copyright © 2016 John Wiley & Sons, Ltd.